Markets and health care : a comparative analysis - Ranade,Wendy(Editor) (Addison Wesley Longman, 1998)
A growing reliance on market disciplines and incentives characterised health care reform strategies in many countries in the 1990s, yet the country which relies most heavily on private health care - the U.S.A. - is the most expensive in the world and still fails to deliver affordable health care to millions of its citizens. This apparent paradox is the starting point for Markets and Health Care: A Comparative Analysis.